The Effect of Using English on The Erosion of Indonesian as A Lingua Franca - Haumahu, Dhino Christy; Abyan, Muhammad Rafiq; Alfarizi, Raihan Bariq; Arochman, Taufik (MIMESIS, 2024)
This research aims to determine the influence of the use of English as a language of daily communication on the erosion of Indonesian as a lingua franca, by considering various sociolinguistic and cultural factors. Indonesian is the national language used by Indonesian people to this day. However, the use of Indonesian seems to be starting to be eroded by the use of English which is recently frequently used, especially by teenagers. This raises growing concerns about its potential impact on the erosion of Indonesian, the lingua franca. This study involves the theory of extensive utilization of the English language in various fields and its current status as a global or international language. The method used in this research was descriptive qualitative. Qualitative data were collected through surveys, online forms, and focus group discussions with individuals representing different linguistic backgrounds and levels of English proficiency. The results of this research showed that 96.2% of respondents always use English as their daily language in communication. Apart from that, the use of English had an impact on the use of Indonesian when having a conversation. Researchers also found that even though respondents knew Indonesian as a lingua franca, in fact they used English more by 51.9%. Therefore, this research also seeks to provide input for language planning and language policy making which aims to maintain the national language and preserve the role of Indonesian as an important communication tool in Indonesian society.